Development Of A Model For Utilizing Basasulsel Wiki As A Local Knowledge–Based Learning Media In Senior High Schools - Siti Arah Suniyah; Alimin Alwi; Supriadi Torro (International journal of technology and education research, 2026)
Abstract This article aims to develop a model for utilizing the BASAsulsel Wiki platform as a local knowledge–based learning medium within the context of implementing the Merdeka Curriculum in secondary schools. This study employs a qualitative approach with a Design-Based Research (DBR) design, combined with a literature review and empirical reflections from the implementation of participatory wikithon workshops in partner schools. The findings indicate that BASAsulsel Wiki functions not only as an information repository but also as a space for knowledge production that encourages active student engagement in identifying social issues, constructing arguments, and publishing their work digitally. The developed learning model integrates three main components: local knowledge, the use of a digital Makassar language dictionary, and students’ active participation in voicing social issues. These components significantly contribute to enhancing digital literacy, critical thinking skills, and students’ social awareness. Furthermore, the integration of local language through digital dictionary features strengthens cultural identity within technology-based learning processes. Conceptually, the novelty of this study lies in the development of a learning model that combines a wiki platform, a participatory wikithon-based approach, and the reinforcement of local wisdom as a contextual, collaborative, and adaptive learning strategy. This model has the potential to be replicated in various educational contexts as an effort to support more meaningful learning transformation in accordance with the demands of the 21st century.